2021
DOI: 10.1177/07342829211057648
|View full text |Cite
|
Sign up to set email alerts
|

Faculty Perceptions of Mattering in Teaching and Learning: A Qualitative Examination of the Views, Values, and Teaching Practices of Award-Winning Professors

Abstract: We summarize qualitative research conducted on the mattering construct and then describe a qualitative investigation focused on mattering as a key aspect of the relational factors which influence the learning and development of students. Semi-structured interviews were conducted with 12 professors recognized for their teaching excellence. Specifically, we assessed professors’ attitudes towards student perceptions of mattering and awareness of mattering in terms of their own self-reported beliefs, attitudes, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…Our participants in both qualitative and quantitative phases reported that positive changes in attitudes toward education included increased enthusiasm, motivation, and confidence in teaching, and a sense of evolution in their perspective on education provided a basis for the capacity development of faculty development programs. This supports the literature demonstrating that positive perceptions are critical and vital for faculty to perform their educational role successfully [ 26 , 27 ].…”
Section: Discussionsupporting
confidence: 87%
“…Our participants in both qualitative and quantitative phases reported that positive changes in attitudes toward education included increased enthusiasm, motivation, and confidence in teaching, and a sense of evolution in their perspective on education provided a basis for the capacity development of faculty development programs. This supports the literature demonstrating that positive perceptions are critical and vital for faculty to perform their educational role successfully [ 26 , 27 ].…”
Section: Discussionsupporting
confidence: 87%
“…Although Formative assessment is common, it tends to be formalized and less effective obviously. The assessment mode has many drawbacks such as difficult to realize the original intention of moral education, biased evaluation results, difficult to improve teaching effects, and easy to mislead students' study and examination [4] . It is an inevitable trend of college teaching evaluation to carry out the reform of assessment mode comprehensively.…”
Section: The Significance Of Formative Assessment Applied To the Teac...mentioning
confidence: 99%
“…The cultivation and promotion of core socialist values [1][2] is a crucial responsibility and role of college English, which is an important humanities course in colleges. The nurturing aspect of the course is not being sufficiently paid attention to by some English teachers at the moment.…”
Section: Introductionmentioning
confidence: 99%